2017
DOI: 10.1021/acsenergylett.7b00842
|View full text |Cite
|
Sign up to set email alerts
|

Postsynthesis Transformation of Insulating Cs4PbBr6 Nanocrystals into Bright Perovskite CsPbBr3 through Physical and Chemical Extraction of CsBr

Abstract: Perovskite-related Cs4PbBr6 nanocrystals present a “zero-dimensional” crystalline structure where adjacent [PbBr6]4– octahedra do not share any corners. We show in this work that these nanocrystals can be converted into “three-dimensional” CsPbBr3 perovskites by extraction of CsBr. This conversion drastically changes the optoelectronic properties of the nanocrystals that become highly photoluminescent. The extraction of CsBr can be achieved either by thermal annealing (physical approach) or by chemical reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
199
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(226 citation statements)
references
References 33 publications
17
199
2
Order By: Relevance
“…The PL spectrum shown in Figure d indicates that the product exhibits a narrow and intense emission band at 517 nm with a full width at half maximum (FWHM) of 24 nm and a 71% absolute PLQY. Obviously, the optical properties of our products are distinct from those well‐crystalline Cs 4 PbBr 6 NCs obtained by the hot‐injection methods . They generally exhibit only a sharp absorption peak at 314 nm and no luminescence under UV light.…”
Section: Resultsmentioning
confidence: 80%
“…The PL spectrum shown in Figure d indicates that the product exhibits a narrow and intense emission band at 517 nm with a full width at half maximum (FWHM) of 24 nm and a 71% absolute PLQY. Obviously, the optical properties of our products are distinct from those well‐crystalline Cs 4 PbBr 6 NCs obtained by the hot‐injection methods . They generally exhibit only a sharp absorption peak at 314 nm and no luminescence under UV light.…”
Section: Resultsmentioning
confidence: 80%
“…13,27 This can be done via the insertion of PbBr 2 , the extraction of CsBr with water or with Prussian Blue, or the extraction of Pb 2+ with amines. 13,27,28,33,37 Several groups have reported that the size and shape of the starting Cs 4 PbBr 6 NCs can be used to tune the size of the final CsPbBr 3 NCs (Figure 5b). 13,27,28,33,37 The transformed CsPbBr 3 NCs exhibit a strong green PL, similar to the PL of directly synthesized CsPbBr 3 NCs, and they show no excitonic absorption in the UV from their parent Cs 4 PbBr 6 NCs (Figure 5c).…”
mentioning
confidence: 99%
“…Palazon et al. have prepared pure Cs 4 PbBr 6 NCs that displayed no PL . The diffractogram of the pristine NCs at room temperature (Figure a, bottom) matched that of bulk Cs 4 PbBr 6 .…”
Section: Pl Of Cs4pbbr6mentioning
confidence: 91%
“… (a) XRD spectra of Cs 4 PbBr 6 NCs upon annealing in vacuum, (b) PL spectra and photographs under a UV lamp (inset) of the original sample and sample annealed at 200 °C . Copyright 2017, American Chemical Society.…”
Section: Pl Of Cs4pbbr6mentioning
confidence: 99%